The Effects of Financial Performance and Macroeconomics on Financial Distress in The Energy Sector Before and During Covid-19 Pandemic - Alya Dinda Nurrahmi; Hermanto Siregar; Bayu Bandono (Business Review and Case Studies, 2023)
The condition of financial distress is where the company's finances are in a bad condition which then becomes an early indicator of bankruptcy for companies to anticipate or restructure so that companies do not experience bankruptcy and liquidation. This study aims to analyze the influence of financial ratios and macroeconomic performance (interest rates, economic growth, and covid-19) on financial distress before and during the Covid-19 pandemic in energy companies listed on the Indonesia Stock Exchange for the period 2017– 2021. The data analysis technique is panel data regression analysis using EViews 12. The population in this study is companies in the energy sector listed on the IDX. The results showed that the condition of financial distress during the pandemic was generally higher than before the Covid-19 pandemic. The results of the analysis conducted in 2017-2021 show that as many as 12 out of 53 companies in the mining sector are experiencing financial distress. A total sample of 12.83% indicated financial distress. Financial ratios and macroeconomic performance (interest rates, economic growth, and covid-19) simultaneously influence financial distress. Partially profitability, liquidity, leverage, and sales growth affect financial distress, while activity, cash flow from the operation, interest rates, economic growth, and covid-19 do not affect financial distress. Keywords: financial distress, financial ratios, macroeconomic performance, probit model